The Integration of Stress Management and Mental Health in Overcoming Burnout to Improve the Quality of Santri Learning - Syamsul Arifin; Chusnul Muali (Journal of Research in Educational Management, 2025)
This research aims to explore and analyze the integration of stress management and mental health in overcoming burnout and its impact on the quality of student learning at the Ar-Rofi'iyyah Kraksaan Probolinggo Islamic Boarding School. This research uses a qualitative method with a case study approach, collecting descriptive data from interviews, observations, and documentation. This method was chosen to provide a direct relationship between researchers and subjects, as well as flexibility in dealing with the complexity of the phenomena being observed. The research results show that burnout in students is caused by several main interrelated factors, including heavy academic load, lack of rest time, social pressure, and physical fatigue due to excessive activity. The implemented stress management and mental health integration program showed positive results, improving the quality of learning through increasing academic scores and active participation of students. In addition, this program reduces health complaints, improves mental well-being, and increases student satisfaction and comfort. Increasing social support, supportive facilities, and mental health education programs are important in creating a more supportive and comfortable Islamic boarding school environment. This research provides an in-depth understanding of how stress management and mental health strategies can overcome burnout and improve the quality of student learning.